RETRACTED: Ppm1b Negatively Regulates 3-Bromopyruvate Induced Necroptosis in Breast Cancer Cells - Sun, Yiming; Pan, Qiong; Ma, Linyan; Chen, Chao; Zhao, Surong; Liu, Hao (Frontiers in Oncology, 2021)
Up to 30% of breast cancer mortality is caused by cancer relapse despite primary clinical treatments due to distant metastases. Further research focusing on breast cancer mechanisms are needed for deeper understanding of disease prognosis. 3-bromopyruvate (3-BP), a glycolysis inhibitor, has been studied as one of the antitumor agents in recent years. In this report we want to investigate cell death forms induced by 3-BP, so we demonstrate the cell proliferation inhibition effect and mechanism of action of 3-BP in breast cancer, both, in vivo and in vitro. We found that 3-BP could inhibit MDA-MB-231 and MCF-7 breast cancer cell proliferation, through energy metabolism inhibition. Further, necroptosis characters in MDA-MB-231 cells after 3-BP treatment were observed, which could be negatively regulated through Ppm1b by dephosphorylation of RIP3. In addition, 3-BP treatment in an MDA-MB-231 cell-transplanted mouse model showed a significant antitumor effect, which correlated with necroptosis-related protein Ppm1b. The findings demonstrate the potential for 3-BP in the treatment of breast cancer, providing impetus for further clinical studies.